Mechanisms Underlying the Anti-inflammatory and Immunosuppressive Activity of Ruxolitinib - Elli, Elena Maria; Baratè, Claudia; Mendicino, Francesco; Palandri, Francesca; Palumbo, Giuseppe Alberto (Frontiers in Oncology, 2019)
The JAK-STAT signaling pathway plays a central role in signal transduction in hematopoietic cells, as well as in cells of the immune system. The occurrence in most patients affected by myeloproliferative neoplasms (MPNs) of driver mutations resulting in the constitutive activation of JAK2-dependent signaling identified the deregulated JAK-STAT signal transduction pathway as the major pathogenic mechanism of MPNs. It also prompted the development of targeted drugs for MPNs. Ruxolitinib is a potent and selective oral inhibitor of both JAK2 and JAK1 protein kinases. Its use in patients with myelofibrosis is associated with a substantial reduction in spleen volume, attenuation of symptoms and decreased mortality. With growing clinical experience, concerns about infectious complications and increased risk of B-cell lymphoma, presumably caused by the effects of JAK1/2 inhibition on immune response and immunosurveillance, have been raised. Evidence shows that ruxolitinib exerts potent anti-inflammatory and immunosuppressive effects; cellular targets of ruxolitinib have been identified among components of both the innate and adaptive immune system, including natural killer, dendritic, T helper, and regulatory T cells. On the other hand, immunomodulatory properties have proven beneficial in some instances, as highlighted by the successful use of ruxolitinib in corticosteroid-resistant graft versus host disease. The objective of this article is to provide an overview of published evidence addressing the key question of the mechanisms underlying ruxolitinib-induced immunosuppression.